Self-Touch as Sociality - Streeck, Jürgen (Social Interaction. Video-Based Studies of Human Sociality, 2020)
Self-touch is often understood as a form of interactional disengagement and withdrawal, of self-involvement, and co-participants are said to disattend ‘self-grooming’ actionsIn this paper, I present interactional sequences during which the parties touch themselves at the same time, or in succession. These data thus suggest that self-touch can also be an engagement display. Approaching self-touch from the ‘point of view’ of idle hands in need of something to do, and of interaction as in need of ongoing mutual coordination, I present cooperative self-touch as a display of the deeply social nature of the human body.